Epigenetics in Schizophrenia: A Pilot Study of Global DNA Methylation in Different Brain Regions Associated with Higher Cognitive Functions - Alelú-Paz, Raúl; Carmona, Francisco J.; Sanchez-Mut, José V.; Cariaga-Martínez, Ariel; González-Corpas, Ana; Ashour, Nadia; Orea, Maria J.; Escanilla, Ana; Monje, Alfonso; Guerrero Márquez, Carmen; Saiz-Ruiz, Jerónimo; Esteller, Manel; et al. (Frontiers in Psychology, 2016)
Attempts to discover genes that are involved in the pathogenesis of major psychiatric disorders have been frustrating and often fruitless. Concern is building about the need to understand the complex ways in which nature and nurture interact to produce mental illness. We analyze the epigenome in several brain regions from schizophrenic patients with severe cognitive impairment using high-resolution (450K) DNA methylation array. We identified 139 differentially methylated CpG sites included in known and novel candidate genes sequences as well as in and intergenic sequences which functions remain unknown. We found that altered DNA methylation is not restricted to a particular region, but includes others such as CpG shelves and gene bodies, indicating the presence of different DNA methylation signatures depending on the brain area analyzed. Our findings suggest that epimutations are not relatables between different tissues or even between tissues' regions, highlighting the need to adequately study brain samples to obtain reliable data concerning the epigenetics of schizophrenia.